2015
DOI: 10.1248/cpb.c14-00699
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Amphiphilic Calixarene Nanoparticles as Delivery Carriers for Paclitaxel

Abstract: Two types of amphoteric calix[n]arene carboxylic acid (CnCA) derivative, i.e., calix[6]arene hexa-carboxylic acid (C 6 HCA) and calix[8]arene octo-carboxylic acid (C 8 OCA), were synthesized by introducing acetoxyls into the hydroxyls of calix[n]arene (n 6, 8). C 6 HCA and C 8 OCA nanoparticles (NPs) were prepared successfully using the dialysis method. CnCA NPs had regular spherical shapes with an average diameter of 180-220 nm and possessed negative charges of greater than 30 mV. C 6 HCA and C 8 OCA NPs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…Encapsulation efficiency (EE) and drug-LC were calculated with the following formula as described previously. [26][27][28] Observed amount of TAC EE (%) 100% Added amount of TAC Weight of TAC in microspheres LC (%) 100% Weight of microspheres…”
Section: Fig 1 Diagrammatic Sketch Of Electrospraying Machinementioning
confidence: 99%
“…Encapsulation efficiency (EE) and drug-LC were calculated with the following formula as described previously. [26][27][28] Observed amount of TAC EE (%) 100% Added amount of TAC Weight of TAC in microspheres LC (%) 100% Weight of microspheres…”
Section: Fig 1 Diagrammatic Sketch Of Electrospraying Machinementioning
confidence: 99%
“…Moreover, poor aqueous solubility and serious side effects associated with commercial preparation of PTx (Taxol ® ) triggered the development of alternative PTx formulations without cremophor. Different nanocarrier systems including nanoparticles, liposomes, micelles, bioconjugates and dendrimers have been employed to improve PTx solubility and eliminate undesired side effects [10][11][12][13][14][15]. It was reported that PTx, delivered in polyanhydrides, was released very slowly, and only 15% of 0.042 mg/mL of PTx was released in 77 days [16].…”
Section: Introductionmentioning
confidence: 99%
“…Since PTx release kinetic is time and medium composition depending, a highly sensitive quantification of drug at short time is required to validate the use of such nanocarriers for drug delivery in cancer therapy. Indeed, due to its high hydrophobicity, most of in vitro studies of PTx release from nanocarriers were performed in simulated physiological medium supplemented with surfactant Tween 80 [11][12][13][14][15][16][17][18]. Numerous analytical methods using liquid phase extraction and solid phase extraction combined to the LC-MS/MS technique were developed for ultrasensitive quantifi- cation of PTx in biological samples such as cells, plasma, urine, feces or tissues [19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several kinds of nanocarriers including liposome, micelle, dendrimer, and nanocrystal have been used for drug delivery systems. 5,[10][11][12] Polymeric micelles were selected as a nanocarrier in this study. Polymeric micelles are self-assembling nanostructure comprising of core and shell which are made up by amphiphilic copolymers.…”
mentioning
confidence: 99%